2014
DOI: 10.1038/srep05345
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Product Developed from Cobalt Nanowires

Abstract: Cobalt nanowires with high aspect ratio have been synthesized via a solvothermal chemical process. Based on the shape anisotropy and orientation of the nanowire assemblies, a record high room-temperature coercivity of 10.6 kOe has been measured in Co nanowires with a diameter of about 15 nm and a mean length of 200 nm. As a result, energy product of the wires reaches 44 MGOe. It is discovered that the morphology uniformity of the nanowires is the key to achieving the high coercivity and high energy density. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
114
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 25 publications
8
114
3
4
Order By: Relevance
“…To the best of our knowledge, this is the first report concerning the use of electron holography and scanning precession-electron diffraction to describe the effect of crystalline orientation on the magnetic structure of high aspect ratio nanowires. Unlike most reports concerning monocrystalline or polycrystalline magnetic nanowires, 30,41,42 in which the formation of domain walls is located along their longitudinal axis (i.e., beyond the tip), for the Co nanowire shown here, no domain wall is observed due to the predominant influence of shape anisotropy along the wire's main axis and to the local competing magnetocrystalline anisotropy axis at the tip. This marked correlation between crystal structure and magnetization distribution is discussed in further detail in the following.…”
Section: Resultscontrasting
confidence: 40%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report concerning the use of electron holography and scanning precession-electron diffraction to describe the effect of crystalline orientation on the magnetic structure of high aspect ratio nanowires. Unlike most reports concerning monocrystalline or polycrystalline magnetic nanowires, 30,41,42 in which the formation of domain walls is located along their longitudinal axis (i.e., beyond the tip), for the Co nanowire shown here, no domain wall is observed due to the predominant influence of shape anisotropy along the wire's main axis and to the local competing magnetocrystalline anisotropy axis at the tip. This marked correlation between crystal structure and magnetization distribution is discussed in further detail in the following.…”
Section: Resultscontrasting
confidence: 40%
“…[22][23][24][25][26][27] In this matter, TEM offers the possibility to combine specialized techniques to investigate structure-property relationships at scales ranging from a few microns to a few nanometers. [28][29][30][31][32][33] For instance, off-axis electron holography affords the study of the magnetization distribution inside nanostructures in a detailed manner, while the coupling of nano-probe scanning and precession electron diffraction is a powerful technique developed to automatically obtain crystallographic orientation/phase maps of nanosized polycrystalline structures. 34 Precession electron diffraction (PED) is a technique that collects electron diffraction patterns under a conical oscillation of the electron beam leading in a significant reduction of the dynamical effects due to the thickness of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Cobased anisotropic nanomaterials are attracting a great part of scientific interest mainly for their possible applications as nanomagnets in (nano)medicine [10] and recording media [11], and as building blocks in high energy nanostructured bulk magnets [12]. All these studies showed that depending on the elaboration process, the nanowires can present very different size, shape, morphology and crystal symmetry as well as very different as-grown spacing between the nano-objects [7,[14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some of the above features are also encountered in fine-particle and nanowire magnetism [ 22,24,[38][39][40][41][42]. For example, fine particles also exhibit a transition from coherent rotation to curling, and wireend features affect the coercivity [24,25,43].…”
mentioning
confidence: 99%